Corneal Higher-Order Aberrations after Descemet's Membrane Endothelial Keratoplasty - Rudolph, Michael; Laaser, Kathrin; Bachmann, Bjoern O.; Cursiefen, Claus; Epstein, Daniel; Kruse, Friedrich (Ophthalmology, 2012)
We compared corneal higher-order aberrations (HOAs) in eyes after Descemet's membrane endothelial keratoplasty (DMEK), Descemet's stripping automated endothelial keratoplasty (DSAEK), and penetrating keratoplasty (PK), and in a control group that had not undergone surgery.Retrospective analysis of clinical data.Thirty eyes of 30 patients who had undergone standard DMEK, 20 eyes of 20 patients after DSAEK, 20 eyes of 20 patients after PK, and 20 eyes of 20 controls were analyzed.In addition to standard postoperative examinations, each participant was analyzed with the Pentacam high-resolution rotating Scheimpflug imaging system (Pentacam HR, Oculus, Wetzlar, Germany). Data were compared between groups.Visual acuity and HOAs.The mean follow-up was 6.5±1.2 months after DMEK, 22.6±11.8 months after DSAEK, and 103.1±74.2 months after PK. There were no statistically significant differences for the anterior 4.0-mm zones between the DMEK group and the controls or between the DMEK and DSAEK groups. The DMEK procedure compared with PK showed statistically significant differences in all terms for the 4.0-mm zones. All combined Zernike terms for mean posterior aberrations of the central 4.0-mm zones showed statistically significant higher aberrations for DMEK compared with controls. The DMEK procedure compared with DSAEK showed statistically significant lower mean values for all combined Zernike terms, except for coma and coma-like terms in the central 4.0-mm zones of the posterior corneal surface. Compared with PK, DMEK showed statistically significant lower mean values for all combined Zernike terms for the central 4.0-mm zones of the posterior corneal surface, except for spherical aberration (SA) and SA-like terms. Best spectacle-corrected visual acuity (BSCVA) after DMEK was statistically significantly better than after DSAEK (P=0.001) and PK (P=0.005). There was no statistically significant difference when BSCVA was compared with controls (P=0.998).Both DSAEK and PK exhibit increased posterior corneal HOAs even years after surgery. Patients receiving DMEK display only slight changes in posterior corneal HOAs.Proprietary or commercial disclosure may be found after the references.
EVALuna2:21073